ENGLISH SPEAKING BARRIERS IN VOCATIONAL EDUCATION: A STUDY OF SMK SPP SNAKMA STUDENTS - Efrizah, Doni; Fadly, Yossy; Putri, Vivi Oxana (Universitas Islam Sumatera Utara, 2024)
The English-speaking skills of students at SMK SPP SNAKMA remain underdeveloped due to specific challenges in using the language within a vocational context. This study explores and analyzes these barriers to understand the underlying factors that hinder effective English communication among vocational students. Employing a qualitative approach, the research gathers data through interviews, observations, and questionnaires to capture students’ perspectives and real-time experiences with English language use. Findings reveal four primary obstacles: limited vocabulary, grammatical difficulties, speaking anxiety, and insufficient practice opportunities. These factors collectively impact students’ confidence and fluency in speaking English, which is critical in vocational settings where practical language skills are increasingly required. The study suggests that a more communicative teaching approach, combined with structured and frequent speaking practice, could significantly address these challenges. By focusing on interactive and supportive teaching methods, educators can create an environment that encourages active language use, helping students overcome barriers and develop essential English-speaking skills for their careers.